A novel technique to prevent distal anterior femoral cortical perforation. Issue 2 (March 2019) - El Beaino, Marc; Chen, Jie; Hagedorn, John C.
Abstract : Background: Anterograde femoral intramedullary nailing is a commonly used operative technique in orthopaedic surgery. Of its related complications, distal femoral anterior cortical breach is of special concern. Methods: We describe the steps of an anterograde femoral intramedullary nailing surgical technique performed on three patients to mitigate their risk of developing an anterior distal perforation of the femoral cortex. Results: All patients presented with a proximal intertrochanteric femoral fracture and underwent an intramedullary femoral nail placement. They all had an anatomic reduction radiographically. No complications intraoperatively or at last follow-up were recorded. Conclusions: By surgically redirecting the guidewire posteriorly before placing the nail in its desired position, our surgical technique prevents the anterior intramedullary nail abutment against the femoral cortex and the risk of anterior femoral cortical perforation. Level of Evidence: V.